Penyuluhan Metode Ekstraksi Atsiri Daun Cengkih Dan Nilam Serta Pemanfaatannya Untuk Siswa SMK N 6 Kendal - Rohadi Rohadi; Devy Angga Gunantar (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The curriculum of the Department of Agricultural Product Processing Technology (APPT) for the 6th State Vocational High School Kendal Regency is designed to produce graduates who have competence in the field of agricultural product processing agribusiness. However in the curriculum there are no subjects on technology of essential spice extraction and the like. In Kendal regency there area plantation of clove and other spices such as red ginger, lemongrass and patchouli, so there is potential for the development of an essential oil refining industry. The Kendal Regency Government is currently developing essential industrial centers in Sukorejo, Patean, Pageruyung and Plantungan Districts. Community Service aims to provide counseling about the essential extraction methods of clove and patchouli leaves and theirs use to students of SMK N 6 Kendal. The Community Service Team carried it out of Friday, November 5, 2022 at the APPT Department Laboratory, which was attended by 20 students and several supervisors. Counseling is carried out using the dissemination methods and class discussion. The results of devotion showed that students’ knowledge of spice processing technology, extraction methods and utilization of essential oil increased. But thecounseling that has been carried out has not been effective in increasing students’ knowledge regarding that topic.